OPTIMISATION OF PRIMER CONCENTRATION AND ANNEALING TEMPERATURE IN PCR TEST METHOD FOR AFRICAN SWINE FEVER VIRUS DETECTION - Luh Dewi Anggreni; Ni Made Ritha Krisna Dewi; I Gusti Ngurah Kade Mahardika; I Gusti Ngurah Narendra Putra (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
African Swine Fever disease causes high fatality number in domestic pigs. The most sensitive and specific laboratory diagnotic is PCR. The successful of PCR is determined by DNA quality, Annealing temperature, MGCl2 concentration, polymerase enzymes, primer concentration, and PCR cycles. The Annealing process requires in the right temperature. The difference annealing temperature causes amplification process failure. The specificity and sensitivity of PCR products are determined by the optimal annealing temperature. PCR optimization, variations of time, temperature, and primer concentration can be adjusted. This study was conducted by PCR testing to detect DNA ASF virus using primer concentration and the most optimum Annealing temperature. Identification of primer concentrations and annealing temperature begins to make PCR components volume 10 µl consist of 5µL PCR Master Mix, a pair of ASF primer 0.5 µl, 1µL DNA templates, and 3µL ddH2O. The PCR component is processed in a thermocycler with a temperature condition of 95°C pre-denaturation for 5 minutes, and denaturation at 94°C for 45 seconds. The gradient annealing temperature starts at 50°C, 52°C, 55°C, 59°Cm and 65°C for 1 minute. Temperature 72 ° C for synthesis 1 minute. repetition of the cycle is 34 times. Final synthesis for 72°C for 5 minutes, the storage temperature is 22°C. The result of optimization at the primer concentration of 10 µm obtained a cleared band according to the target compared to the primary concentration of 5 µm. The best annealing temperature in this research is 55 °C. If the Annealing temperature is given lower, causing primer attachment to the DNA template is not specific so non-specific PCR products are formed many bands. Conversely, if the annealing temperature is higher, causing primary attachment to the template DNA will be released so that the band that appears is very thin PCR product is not formed does not appear.